Catalytic Methods for CH Bond Functionalization: Application in Organic Synthesis - Kakiuchi, Fumitoshi; Chatani, Naoto (Advanced synthesis & catalysis, 2003)
The development of catalytic reactions involving carbon‐hydrogen bond cleavage is currently one of the most attractive research subjects in organic and organometallic chemistry. About 40 years have past since the pioneering report of the cleavage of CH bonds with transition metal complexes. Since that time, a vast number of studies of the cleavage of CH bonds, using stoichiometric amounts of transition metal complexes has appeared. In the last decade, a variety of catalytic reactions involving CH bond cleavage has been reported. In this review we briefly survey the results of these research activities with respect to the catalytic use of unreactive CH bonds in organic synthesis.